Surface Evaporative Capacitance: How Soil Type and Rainfall Characteristics Affect Global‐Scale Surface Evaporation. Issue 1 (23rd January 2019) - Or, D.; Lehmann, P.
Abstract: The separation of evapotranspiration (ET) into its surface evaporation ( E ) and transpiration ( T ) components remains a challenge despite its importance for linking water and carbon cycles, for water management, and for attribution of hydrologic isotope fractionation. Regional and global estimates of surface evaporation often rely on estimates of ET (e.g., Penman‐Monteith) where E is deduced as a residual or as a fraction of potential evaporation. We propose a novel and direct method for estimating E from soil properties considering regional rainfall characteristics and accounting for internal drainage dynamics. A soil‐dependent evaporative characteristic length defines an active surface evaporative capacitor depth below which soil water is sheltered from capillary pull to the evaporating surface. A site‐specific evaporative capacitor is periodically recharged by rainfall and discharges at rates determined by interplay between internal drainage and surface evaporation. The surface evaporative capacitor concept was tested using field measurements and subsequently applied to generate a global map of climatic surface evaporation. Latitudinal comparisons with estimates from other global models (e.g., Penman‐Monteith method modified by Leuning et al., 2008, https://doi.org/10.1029/2007WR006562 [PML]; Moderate Resolution Imaging Spectroradiometer [MODIS]; and Global Land‐surface Evaporation: the Amsterdam Methodology [GLEAM]) show good agreement but also point to potential shortcomings of present estimates of surface evaporation. Interestingly, the ratio of surface evaporation ( E ) to potential evapotranspiration (ET0 ) is relatively constant across climates, biomes, and soil types with E /ET0  < 0.15 for 60% of all terrestrial surfaces, in agreement with recent studies. Key Points: A novel method for estimating surface evaporation from soil properties and accounting for internal drainage dynamics is presented A soil‐dependent evaporative characteristic length defines an active surface evaporative capacitor (SEC) depth The ratio of surface evaporation to potential evapotranspiration is relatively constant across climates, biomes, and soil types